2006
DOI: 10.1159/000098058
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Sensorimotor Peripheral Neuropathy in Type 2 Diabetes

Abstract: Background: The mechanisms responsible for the onset of sensorimotor peripheral diabetic neuropathy (SMPN) remain largely unknown. To address this issue, we studied the relationship between traditional cardiovascular risk factors, parameters of metabolic control, and the presence of SMPN in patients with type 2 diabetes of relatively short duration. Methods: Blood pressure, glycated hemoglobin, lipid profile, and the presence of micro- and macrovascular complications were assessed and monitored in 31 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…[18191621] Our figures showed a numerical higher occurrence of DPN among smokers and patients with high BP, hypercholesterolemia and potential microalbuminuric /proteinuric, but like others[1612] we could not identify them as statistically significant risk factors. This is in contrast with other reports,[212324] and may have been due to the limited sample size.…”
Section: Discussioncontrasting
confidence: 96%
“…[18191621] Our figures showed a numerical higher occurrence of DPN among smokers and patients with high BP, hypercholesterolemia and potential microalbuminuric /proteinuric, but like others[1612] we could not identify them as statistically significant risk factors. This is in contrast with other reports,[212324] and may have been due to the limited sample size.…”
Section: Discussioncontrasting
confidence: 96%
“…A possible explanation might be that in type 1 diabetes, MG mainly derives from glucose whereas in type 2, due to frequently associated hypercholesterolemia, lipids might be another important source for MG [ 14 ] . Moreover, there are other risk factors like obesity and hypertension which are mainly associated with type 2 diabetes and contribute to the pathogenesis of neuropathy [ 15 ] . Therefore, not only metabolic changes in glucose associated pathways but also elevated LDL and triglyceride levels can lead to MG accumulation in diabetics [ 14 ] , which might also explain the prevention or improvement of late diabetic complications by treating hypercholesterolemia [ 16 , 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Some found no impact of weight, systolic and diastolic blood pressure, neuropathy duration, and plasma cholesterol or triglyceride levels (17) but also suggested that vascular factors participate in the development of neuropathy (18), whereas others reported an independent association between pulse pressure and hypertension and diabetic peripheral neuropathy in patients with type 2 diabetes (19). A prospective study of 57 patients with type 2 diabetes did not confirm these findings (20).…”
Section: Discussionmentioning
confidence: 99%